1988
DOI: 10.1083/jcb.106.2.269
|View full text |Cite
|
Sign up to set email alerts
|

A chloroquine-resistant Swiss 3T3 cell line with a defect in late endocytic acidification

Abstract: Abstract. To investigate the role of acidification in cell proliferation, several cell lines resistant to chloroquine were isolated with the expectation that some would express altered endocytic acidification. The preliminary characterization of one of these lines, CHL60-64, is described. In contrast to endocytic mutants described previously, the initial phase of endocytic acidification, as measured by transferrin acidification, is normal in this cell line. However, a difference in subsequent endocytic acidifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 22 publications
5
20
0
Order By: Relevance
“…Interestingly, CpG-induced phosphorylation of Erk1/2 was not inhibited by YM201636 (Figure 7A), which suggested that it is not dependent on the endosomal localization of CpG. Chloroquine, which inhibits endosome acidification [21], showed similar effects to YM201636 on the TLR-induced phosphorylation of signaling molecules (Figure 7A). CpG-induced Stat3 phosphorylation but not LPS-induced Stat3 phosphorylation, was inhibited by both YM201636 and by the knockdown of PIKfyve (Figure 7B).…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, CpG-induced phosphorylation of Erk1/2 was not inhibited by YM201636 (Figure 7A), which suggested that it is not dependent on the endosomal localization of CpG. Chloroquine, which inhibits endosome acidification [21], showed similar effects to YM201636 on the TLR-induced phosphorylation of signaling molecules (Figure 7A). CpG-induced Stat3 phosphorylation but not LPS-induced Stat3 phosphorylation, was inhibited by both YM201636 and by the knockdown of PIKfyve (Figure 7B).…”
Section: Resultsmentioning
confidence: 92%
“…AO is a weak base which accumulates into acidic compartments (32)(33)(34). When present at high concentrations, it forms complexes, resulting in a shift in fluorescence from green to red.…”
Section: Resultsmentioning
confidence: 99%
“…Most agree that accumulation of amines into lysosomes occurs predominantly according to a process referred to as pH‐partitioning; however, it is important to realize that not every cell line has normally acidified lysosomes and endocytic compartments and as a result, such accumulations might not pertain to all cells 10–12. A simplified model of this mechanism is depicted in Figure 1.…”
Section: Mechanistic Basis For Lysosomal Sequestration Of Aminesmentioning
confidence: 99%